Sosialisasi Pengelolaan Bank Sampah Untuk Meningkatkan Perkembangan Desa dan Lingkungan Bersih di Dusun Cilutung - Alya Fitri Nur Rahmadanti; Haldy Hendryansyah; Lintang Adistya Sari; Tabrani Sjafrizal (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
The management of the waste bank in Cilutung hamlet is carried out as a solution to reduce the volume of waste which is already very large. Increasing the population in the Cilutung hamlet is accompanied by an increase in the volume of waste in the Cilutung hamlet. It is not only waste that has an impact on the environment but also the disposal and decomposition system of the community which can cause environmental damage and become a problem point in the Cilutung hamlet. The main objective of the processing of the GELISAH waste bank is to be the main solution in achieving the main target of the hamlet to be better. Waste bank processing is carried out to improve village development and a clean environment in Cilutung Hamlet through the GELISAH socialization (Waste Care Movement). Socialization is about waste bank management, waste utilization, types of waste, good use of organic waste against maggot, utilization of ECOBRICK waste from plastic bottle waste. The end result of this work program is reducing the volume of waste and establishing a waste bank in the Cilutung hamlet, and increasing public awareness and concern for village development and a clean environment around it.